2010
DOI: 10.1093/cercor/bhq009
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Active States in Local Neocortical Networks during Slow Sleep Oscillation

Abstract: Slow-wave sleep is characterized by spontaneous alternations of activity and silence in corticothalamic networks, but the causes of transition from silence to activity remain unknown. We investigated local mechanisms underlying initiation of activity, using simultaneous multisite field potential, multiunit recordings, and intracellular recordings from 2 to 4 nearby neurons in naturally sleeping or anesthetized cats. We demonstrate that activity may start in any neuron or recording location, with tens of millis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
269
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(301 citation statements)
references
References 63 publications
30
269
2
Order By: Relevance
“…Previous investigations showed large cortical oscillatory power in a wide frequency band (10 -200 Hz) during up-states, while the spectral power was much smaller during down-states. Our findings are in a perfect match with these reports [2,3,16]. Consistent with prior studies in animals, we have shown that the up-state was associated with increased firing and elevated spindle and gamma power during the surface-positive LFP half-wave, while the down-state was characterized by the widespread surface-negative LFP half-wave with decreased firing, and oscillatory activity.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous investigations showed large cortical oscillatory power in a wide frequency band (10 -200 Hz) during up-states, while the spectral power was much smaller during down-states. Our findings are in a perfect match with these reports [2,3,16]. Consistent with prior studies in animals, we have shown that the up-state was associated with increased firing and elevated spindle and gamma power during the surface-positive LFP half-wave, while the down-state was characterized by the widespread surface-negative LFP half-wave with decreased firing, and oscillatory activity.…”
Section: Discussionsupporting
confidence: 93%
“…More specifically, we found that the LFP is rhythmic at about 1 Hz; its depth profile well corresponds to previous findings, where the LFP inversion was taking place in layer III corresponding to a depth about 300 -500 μ m below the cortical surface [2,3,16]. We have also shown that the bimodality of the oscillation using MUA measures can be reliably characterized, which is also in correspondence with the basic properties of SWA and previous findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Simultaneous recordings of cortical intracellular activity and LFP showed that the SWs reflect synchronized activity of large groups of cortical neurons that nearly simultaneously alternate between depolarized and hyperpolarized states [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%